The Effect Of Training, Organizational Support, And Job Satisfaction On Turnover Intention Of Internship Students In The Special Region Of Yogyakarta - Achmad Fauzi; Alldila Nadhira Ayu Setyaning (Cita konsultindo, 2024)
This study investigates the impact of training, organizational support, and job satisfaction on turnover intention among intern students in the Special Region of Yogyakarta. The research focuses on Millennials, who make up over 50% to 70% of the workforce and pose unique challenges in recruitment and retention due to generational differences. Using quantitative methods, the study surveyed 260 respondents, with data analyzed through SmartPLS (v.3.2.9). The findings reveal that training does not significantly impact turnover intention or job satisfaction but positively influences organizational support. Organizational support reduces turnover intention and enhances job satisfaction, which in turn decreases turnover intention. Companies need to improve training and support to increase employee satisfaction and retention.